He calls me by lightning : the life of Caliph Washington and the forgotten saga of Jim Crow, southern justice, and the death penalty - Bass, S. Jonathan (Liveright Publishing Corporation, 2017)
"... reconstruction of the ... life of a wrongfully convicted man whose story becomes an historic portrait of the Jim Crow South"--